Information literacy mission in digital environment: a prospects and plans for developing society in India - SUDHIR KUMAR SUBHAJIT CHOUDHURY LEENA SHAH (World Library and Information Congress: 70th IFLA General Conference and Council, 2004)
The paper correlates literacy and information literacy. Searches reasons of illiteracy in India. Discusses present situation of literacy rate, educational institutions, Public Library Acts and digital divide. Gives the meaning of literacy and information literacy in Indian context. Gives role of Community and Library Information Centres. Information networks available for dissemination are presented in brief. Relation between e-governance and information literacy have been discussed. Some information literacy programs initiated are given. Suggests for an Information Literacy Plan for various community to take India to Millennium 2020.Recommends for a national apex body, development of CLIN and amendments in public library acts to meet challenges of digital information society